Mechanical behavior of additive manufactured wood-based composites for construction - Milinda Yapa Hamillage; Robert Carne; Armando G McDonald; Michael Maughan; Ahmed A Ibrahim; Daniel J Robertson (Sustainable Structures)
Additive manufacturing of composites composed of wood residues and ecofriendly binders such as sodium silicate could reduce the carbon footprint of the construction industry. In this paper the spatially varying mechanical behavior of a single layer of a 3D-printed wood-sodium silicate composite with a 50:50 wt.% known as PrinTimber was investigated. Flexural testing revealed the outer edges of a single printed layer of composite material exhibited greater strength compared to the inner regions of the same sample. Furthermore, tensile tests demonstrated that the longitudinal modulus of elasticity of a single layer was lower than the transverse modulus of elasticity of the same layer. Optical images revealed the 3D printing process tended to arrange wood fibers in a particular manner. The unique fiber arrangement within the layer explains the observed directional dependent response of the sample.